Pendidikan Moral Perspektif Emile Durkheim Relevansinya Bagi Pendidikan di Indonesia - Paulina Virgianti; Silfia Hanani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This research aims to describe Emile Durkheim's theory of moral education and its relevance to children's education, especially in the Indonesian context. Qualitative research with a narrative study approach is used to collect information from various literature sources, including books, journals, magazines and the internet, which is appropriate to the focus of the problem raised. Emile Durkheim, a pioneer in sociology, explained that moral education is an important foundation in developing individuals who have high social and moral awareness. For him, morality is not only related to individual rules, but is closely related to social norms that enable harmonious living in society. Durkheim's theory is relevant in overcoming the challenges of moral education in Indonesia, including moral decay, globalization, pluralism and radicalism. The implication is to encourage the development of a curriculum that integrates general lessons with religious and moral subjects, organizes extracurricular activities that encourage cooperation and creativity, and applies active and critical learning methods. Durkheim's concept provides relevant guidance for the moral education of children in Indonesia. Applying this theory can help children understand universal values, build involvement in the community, and strengthen collective awareness of the values that bind society. Educational measures such as synchronized integration, extracurricular activities, and the use of active learning methods are key in creating a learning environment that supports holistic moral development for children in Indonesia.